Grassroots : - Fawcett, Susan (Houghton Mifflin Company, 1976)
Motivating students with high-interest content and guiding them with a clear, functional approach, Susan Fawcett's Grassroots inspires students to succeed. With its excellent writing instruction, well-crafted exercises, and engaging writing activities, Grassroots teaches students how to write correct sentences and effective paragraphs. Fawcett introduces each topic with a boxed example and follows it up with clear, easy to read explanations. After the boxed example, Grassroots engages students with bulleted points and questions before defining the rule. Then, Grassroots inspires students and reinforces concepts with a wealth of interesting examples and practice that lead students from carefully controlled practice toward creating their own successful sentences and paragraphs.